2016
DOI: 10.1097/tp.0000000000001398
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Hepatic Trauma

Abstract: Liver transplantation seems to be justified in selected patients with otherwise fatal severe liver injuries, particularly in whom cross-clamping without extracorporeal bypass can be omitted. The ISS cutoff less than 33 may be useful in the selection process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Apart from HCC and high MELD scores, several other conditions are reported to be associated with particularly poor posttransplant outcomes resembling that of the highest-risk HCC patients, such as retransplantation for hepatitis C virus recurrence, trauma, and unresectable neuroendocrine tumors metastases. 25 , 30 , 31 Considering survival benefit, it is the high-risk HCC patients and non-HCC patients that are reported to benefit most from undergoing LT. 18 , 32 , 33 However, pretransplant alpha-fetoprotein was previously found to be inversely correlated with transplant benefit. 34 Therefore, potential expansion of the selection criteria into patients with high alpha-fetoprotein should be considered with great caution considering both transplant utility and benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from HCC and high MELD scores, several other conditions are reported to be associated with particularly poor posttransplant outcomes resembling that of the highest-risk HCC patients, such as retransplantation for hepatitis C virus recurrence, trauma, and unresectable neuroendocrine tumors metastases. 25 , 30 , 31 Considering survival benefit, it is the high-risk HCC patients and non-HCC patients that are reported to benefit most from undergoing LT. 18 , 32 , 33 However, pretransplant alpha-fetoprotein was previously found to be inversely correlated with transplant benefit. 34 Therefore, potential expansion of the selection criteria into patients with high alpha-fetoprotein should be considered with great caution considering both transplant utility and benefit.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 We found that 9.7% of patients transplanted for trauma were listed as status 1A (acute liver failure), with no significant differences in long-term graft and patient survival compared with those listed under a different status. A study analyzing the European Liver Transplantation registry by Krawczyk et al 9 reported that patients receiving OLT for hepatic trauma had 5-year patient and graft survival rates of 50.7% and 44.9%, respectively, with a notably high 90-day mortality rate of 42.5%. In contrast, we found a 90-day mortality rate of 8.3%, which was not significantly higher than that of the matched control group transplanted for other indications.…”
Section: Discussionmentioning
confidence: 99%
“…Orthotopic liver transplantation is reserved as an alternative treatment for selected patients with complex hepatic injuries. In extreme cases, two-stage total hepatectomy followed by OLT with a portosystemic shunt for up to 36 hours has been described as a salvage procedure for life-threatening injuries 8–33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grade V–VI injuries are associated with hepatic avulsion or porta hepatis injury (grade III, Niamieno et al ). [3] It suppose such a challenge for any surgeon that, in extreme cases, liver transplantation may be the best therapeutic option [4].…”
Section: Introductionmentioning
confidence: 99%